PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VI SDN 071020 AWA’AI DITINJAU DARI SELF CONFIDENCE - Mendrofa, Rosdiati; amelia, Mira; Novianti, Idha; syahril, Syahril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students' mathematics learning outcomes and self-confidence, indicating the need for an innovative instructional approach that enhances both cognitive and affective aspects of learning. One alternative is the Project-Based Learning (PjBL) model, which emphasizes students' active engagement through authentic projects to solve real-world problems and produce tangible products. This study aimed to: (1) examine the effect of the Project-Based Learning model on students' mathematics learning outcomes; (2) analyze the effect of self-confidence on students' mathematics learning outcomes; and (3) investigate the interaction between the Project-Based Learning model and self-confidence on the mathematics learning outcomes of sixth-grade students at SDN 071020 Awa’ai in the topic of cubes and rectangular prisms. This study employed a quantitative approach using a quasi-experimental method with a 2 × 2 factorial design. Data were analyzed using a Two-Way Analysis of Variance (Two-Way ANOVA) with unequal cell sizes after satisfying the assumptions of normality and homogeneity. The findings revealed that: (1) the Project-Based Learning (PjBL) model had a significant positive effect on students' mathematics learning outcomes, with students taught using PjBL achieving better results than those taught using the conventional learning model; (2) self-confidence had a significant effect on students' mathematics learning outcomes; and (3) there was a significant interaction between the learning model and self-confidence in influencing students' mathematics learning outcomes. These findings indicate that the implementation of the Project-Based Learning model, supported by students' self-confidence, is effective in improving mathematics learning outcomes.